A kind of high-strength and high-toughness regenerated cellulose hydrogel beads and preparation method

By chemically modifying cellulose and dissolving it in a pre-cooled alkali solution, it is dripped into the regeneration liquid to cure, which solves the problem of low mechanical strength of cellulose hydrogel beads in the prior art, and achieves high-strength and high-toughness bead preparation, with wide application prospects.

CN119161602BActive Publication Date: 2025-03-11THE SECOND AFFILIATED HOSPITAL OF NAVAL MEDICAL UNIVERSITY PLA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411679298.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The prior art when preparing spherical cellulose hydrogel beads, the mechanical strength is not high, fragile and easy to break, which limits its practical application.

Method used

By chemically modifying cellulose, the modified cellulose is dissolved in a pre-cooled alkali solution by using the method of weakening the hydrogen bonding between cellulose. The modified cellulose solution is prepared, and then it is dripped into the regeneration liquid to cure it into high-strength and high-toughness cellulose hydrogel beads.

Benefits of technology

The preparation of high-strength and high-toughness cellulose hydrogel beads has been realized, which reduces the dissolution difficulty and energy consumption, simplifies the preparation method, has high mechanical strength and toughness, and is suitable for biomedical and environmental ecology fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161602B_ABST
    Figure CN119161602B_ABST
Patent Text Reader

Abstract

The present invention is applicable to the technical field of functional materials, and relates to a high-strength and high-toughness regenerated cellulose hydrogel beads and a preparation method, the preparation method comprising the following steps: chemically modifying cellulose, using a chemical modification method that weakens the hydrogen bonding between cellulose molecules; dissolving the modified cellulose in a precooled alkaline solution to obtain a uniform cellulose solution; dripping the cellulose solution into a regeneration liquid to solidify into cellulose hydrogel beads. The present invention first modifies the cellulose and then dissolves it, which greatly reduces the difficulty and energy consumption of dissolution. The preparation method is simple, has high strength and toughness, and the beads after regeneration have evenly distributed corresponding functional groups, which can be applied in different directions, and can realize the one-step preparation of functionalized cellulose hydrogel beads.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to high-strength and high-toughness regenerated cellulose hydrogel beads and a preparation method thereof. Background Art

[0002] Cellulose molecules are composed of a large number of repeated anhydroglucose units. Each glucose unit has three free hydroxyl groups. Especially after cellulose is dissolved, the crystalline region of cellulose is opened, releasing a large number of free hydroxyl groups, which significantly improves the accessibility and reactivity of cellulose. By introducing groups with specific functionalities, cellulose can be modified to give it a variety of excellent properties, so that it can be used in a variety of fields.

[0003] Currently, when preparing spherical cellulose hydrogel beads, the spherical beads are generally prepared first and then modified. However, the materials obtained by this preparation method generally do not have very high mechanical strength and are mostly very fragile and easy to break, which seriously limits their practical application. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a method for preparing high-strength and high-toughness regenerated cellulose hydrogel beads, aiming to solve the problems raised in the above-mentioned background technology.

[0005] The embodiment of the present invention is implemented as follows: a method for preparing high-strength and high-toughness regenerated cellulose hydrogel beads comprises the following steps:

[0006] Chemically modifying the cellulose by weakening the hydrogen bonding between cellulose molecules;

[0007] dissolving the modified cellulose in a precooled alkaline solution to prepare a uniform cellulose solution;

[0008] The cellulose solution is dripped into the regeneration liquid and solidified into cellulose hydrogel beads.

[0009] Preferably, the chemical modification method is one of sulfonation, phosphorylation, TEMPO oxidation and carboxymethylation.

[0010] Preferably, when the chemical modification method adopts carboxymethylation, the degree of carboxymethyl substitution is 0-3.

[0011] Preferably, the alkaline solution is a mixture of one or more of LiOH, KOH, NaOH, CsOH, and Ca(OH)2.

[0012] Preferably, the concentration of the alkaline solution is 0.5-20 wt.%.

[0013] Preferably, the precooling temperature of the alkaline solution is -30-10°C.

[0014] Preferably, the concentration of the cellulose solution is 1-15 wt.%.

[0015] Preferably, the regeneration liquid is a mixture of one or more of acetic acid, sulfuric acid, hydrochloric acid, ethanol, acetone, sodium sulfate, ammonium sulfate, zinc sulfate, and water.

[0016] Another object of an embodiment of the present invention is to provide a regenerated cellulose hydrogel bead with high strength and high toughness, which is prepared by the above preparation method.

[0017] The embodiment of the present invention provides a method for preparing high-strength and high-toughness regenerated cellulose hydrogel beads, in which cellulose is first modified and then dissolved, which greatly reduces the difficulty and energy consumption of dissolution. The preparation method is simple, has high strength and toughness, and the beads after regeneration have evenly distributed corresponding functional groups, which can be applied in different directions. It can realize the one-step preparation of functionalized cellulose hydrogel beads, which is of great significance in many fields such as biomedicine and environmental ecology. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a photo of the regenerated cellulose step provided in Example 1 of the present invention;

[0019] Figure 2 A photograph of carboxymethyl cellulose beads in regeneration solution provided in Example 1 of the present invention;

[0020] Figure 3 The photographs of carboxymethyl cellulose beads injected using three different syringe sizes provided in Example 1 of the present invention;

[0021] Figure 4 SEM image of carboxymethyl cellulose beads provided in Example 1 of the present invention (the left side is a schematic diagram of the entire bead, the middle is a schematic diagram of the surface of the bead, and the right side is a schematic diagram of the cross-section of the bead);

[0022] Figure 5 The mechanical strength test results of the carboxymethyl cellulose beads provided in Example 1 of the present invention;

[0023] Figure 6 Compression test results of a single carboxymethyl cellulose bead provided in Example 1 of the present invention;

[0024] Figure 7 The cyclic compression test results of the carboxymethyl cellulose bead accumulation model provided in Example 1 of the present invention;

[0025] Figure 8The standard curve of carboxymethyl cellulose beads adsorbing low-density lipoprotein provided in Example 1 of the present invention and the comparison chart of protein concentration before and after adsorption;

[0026] Fig. 9 Schematic diagram of the adsorption of heavy metal iron ions by carboxymethyl cellulose beads provided in Example 2 of the present invention (the left side is a photo of the adsorption of heavy metal iron ions for 0 minutes, the middle is a photo of the adsorption of heavy metal iron ions for 5 minutes, and the right side is a photo of the adsorption of heavy metal iron ions for 10 minutes);

[0027] Fig.10 A comparison diagram of carboxymethyl cellulose beads that adsorb heavy metal iron ions and those that do not adsorb heavy metal iron ions provided in Example 2 of the present invention;

[0028] Fig.11 A comparison diagram of carboxymethyl cellulose beads adsorbing heavy metal copper ions and carboxymethyl cellulose beads not adsorbing heavy metal copper ions provided in Example 3 of the present invention;

[0029] Fig.12 This is a photo of the magnetic sulfonate cellulose beads provided in Example 4 of the present invention;

[0030] Fig.13 Schematic diagram of the magnetic adsorption capacity of magnetic sulfonate cellulose beads provided in Example 4 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0032] A high-strength and high-toughness regenerated cellulose hydrogel bead, the preparation method of which comprises the following steps:

[0033] (1) Chemically modifying cellulose;

[0034] The sources of the cellulose include industrial cellulose raw materials, such as cotton pulp, wood pulp, bamboo pulp, bagasse, etc., and natural raw materials rich in cellulose, such as wood, cotton, straw, bamboo, etc., preferably wood pulp;

[0035] The chemical modification methods include but are not limited to sulfonation, phosphorylation, TEMPO oxidation, carboxymethylation, and any other chemical modification methods that can weaken the hydrogen bonding between cellulose molecules; preferably carboxymethylation, wherein the degree of carboxymethyl substitution of the carboxymethyl cellulose is 0-3, preferably 0.5;

[0036] (2) dissolving the modified cellulose in a pre-cooled alkaline solution of a certain concentration to obtain a uniform cellulose solution;

[0037] Wherein, the alkaline solution is a mixture of one or more single-component alkaline solutions such as LiOH, KOH, NaOH, CsOH, Ca(OH)2, etc., preferably a NaOH solution;

[0038] The concentration of the alkaline solution is 0.5-20 wt %, preferably 8%, and the precooling temperature of the alkaline solution is -30-10°C, preferably 0°C;

[0039] The concentration of the cellulose solution is 1-15 wt.%, preferably 10 wt.%;

[0040] (3) dripping the cellulose solution into the regeneration liquid through a syringe to solidify into cellulose hydrogel beads with different diameters / sizes;

[0041] Wherein, the regeneration liquid is a mixture of one or more of acetic acid, sulfuric acid, hydrochloric acid, ethanol, acetone, sodium sulfate, ammonium sulfate, zinc sulfate, and water, preferably sulfuric acid;

[0042] The diameter of the syringe is in the range of 50-300 μm, preferably 200 μm.

[0043] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0044] Example 1: A high-strength and high-toughness regenerated cellulose hydrogel bead, the preparation method of which comprises the following steps:

[0045] (1) Cellulose modification: The cellulose material is modified by carboxymethylation to obtain carboxymethyl cellulose with a degree of substitution of 0.35 (the specific modification method refers to the etherification technology in the prior art);

[0046] (2) Dissolving cellulose: 10 g of carboxymethyl cellulose with a carboxymethyl substitution degree of 0.35 was weighed and dissolved in 90 g of a 6% sodium hydroxide aqueous solution (precooled at 0°C) to obtain a cellulose solution;

[0047] (3) Regeneration of cellulose: Pour the dissolved cellulose solution into a syringe, load it onto a peristaltic pump and slowly drip the cellulose solution into 10% sulfuric acid (such as Figure 1 As shown), transparent carboxymethyl cellulose beads (as shown Figure 2 as shown).

[0048] Performance Analysis:

[0049] (1) Morphology analysis: The carboxymethyl cellulose beads prepared in Example 1 were observed using an optical camera, and the results were as follows: Figure 3 As shown, according to Figure 3It can be seen that the beads prepared in Example 1 are transparent regular spheres as a whole. Using syringes with different apertures, beads with diameters ranging from 1 to 2 mm can be obtained. The results obtained by scanning electron microscopy are as follows: Figure 4 As shown, according to Figure 4 It can be seen that the diameter of the condensed beads is about 2 mm, the surface is a relatively rough structure, and the interior is a 3D honeycomb structure;

[0050] (2) Mechanical strength test: The carboxymethyl cellulose beads prepared in Example 1 were subjected to a mechanical strength test, and the results were as follows: Figure 5 As shown, according to Figure 5 It can be seen that the compressive stress of the gel exceeds 3 MPa when the compression deformation is 80%, while the traditional pure natural polysaccharide gel will break when the stress reaches 0.8 MPa (Int J BiolMacromol. 2018Oct1:117:392-400.);

[0051] A single carboxymethyl cellulose bead with a diameter of 2 mm prepared in Example 1 was subjected to a compression test with a displacement of 2.0 mm (as shown in FIG. Figure 6 As shown on the left, a single bead can withstand a pressure of more than 5 N and deform more than 90% without breaking (as shown on the left). Figure 6 As shown on the right); a plurality of carboxymethyl cellulose beads prepared in Example 1 were placed in a beaker to form a tightly packed model, and a cyclic compression test was performed on the stacked model (as shown in FIG. Figure 7 left), they remain elastic after repeated compression (e.g. Figure 7 center), and can withstand pressures exceeding 100 N (as shown in Figure 7 As shown on the right); However, the traditional polysaccharide beads without cross-linking agent are easily broken when the compression deformation exceeds 50% (Int J Biol Macromol. 2018 Oct1: 117: 392-400.);

[0052] In summary, the carboxymethyl cellulose beads prepared in the embodiment of the present invention have excellent strength and toughness compared with the traditional pure natural polysaccharide beads;

[0053] (3) Analysis of the ability to adsorb low-density lipoprotein, including the following steps:

[0054] Human low-density lipoprotein was diluted with phosphate buffer to a final concentration of 40 μg / ml. 0.6 g of carboxymethyl cellulose beads prepared in Example 1 were mixed with 2 mL of human low-density lipoprotein solution, and the mixture was incubated at 37°C with gentle shaking for 2 h. The concentration of low-density lipoprotein in the solution was detected, and the results were as follows: Figure 8 As shown, according to Figure 8It can be seen that the concentration of low-density lipoprotein in the solution was 40 μg / ml before adsorption and decreased to 13 μg / ml after adsorption.

[0055] Example 2: A high-strength and high-toughness regenerated cellulose hydrogel bead, the preparation method of which comprises the following steps:

[0056] (1) Cellulose modification: The cellulose material is modified by carboxymethylation to obtain carboxymethyl cellulose with a degree of substitution of 0.35;

[0057] (2) Dissolving cellulose: 10 g of carboxymethyl cellulose with a carboxymethyl substitution degree of 0.35 was weighed and dissolved in 90 g of a 6% sodium hydroxide aqueous solution (precooled at 0°C) to obtain a cellulose solution;

[0058] (3) Regenerated cellulose: Pour the dissolved cellulose solution into a syringe, load it onto a peristaltic pump and slowly drip the cellulose solution into 10% sulfuric acid to obtain transparent carboxymethyl cellulose beads.

[0059] Performance Analysis:

[0060] The analysis of the ability to adsorb heavy metal iron ions includes the following steps:

[0061] Ferric chloride was diluted with deionized water to a final concentration of 0.01 mol / L. 0.6 g of carboxymethyl cellulose beads prepared in Example 2 were mixed with 10 mL of ferric chloride solution and incubated at 37°C with gentle shaking for 10 min. Fig. 9 As shown, the carboxymethyl cellulose beads in the solution were taken out and compared with the carboxymethyl cellulose beads that were not mixed with the ferric chloride solution. The results are as follows Fig.10 As shown, according to Fig.10 It can be seen that the color of the carboxymethyl cellulose beads mixed with the ferric chloride solution turned dark brown, proving its ability to adsorb heavy metal iron ions.

[0062] Example 3: A method for preparing a high-strength and high-toughness regenerated cellulose hydrogel bead comprises the following steps:

[0063] (1) Cellulose modification: The cellulose material is modified by carboxymethylation to obtain carboxymethyl cellulose with a degree of substitution of 0.15;

[0064] (2) Dissolving cellulose: 10 g of carboxymethyl cellulose with a carboxymethyl substitution degree of 0.15 was weighed and dissolved in 90 g of a 6% sodium hydroxide aqueous solution (precooled at 0°C) to obtain a cellulose solution;

[0065] (3) Regenerated cellulose: Pour the dissolved cellulose solution into a syringe, load it onto a peristaltic pump and slowly drip the cellulose solution into 10% sulfuric acid to obtain transparent carboxymethyl cellulose beads.

[0066] Performance Analysis:

[0067] The analysis of the ability to adsorb heavy metal copper ions includes the following steps:

[0068] Copper sulfate was diluted with deionized water to a final concentration of 0.01 mol / L. 0.6 g of carboxymethyl cellulose beads prepared in Example 3 were mixed with 10 mL of copper sulfate solution and incubated at 37°C with gentle shaking for 10 min. The carboxymethyl cellulose beads in the solution were taken out and compared with the carboxymethyl cellulose beads not mixed with the copper sulfate solution. The results are as follows: Fig.11 As shown, according to Fig.11 It can be seen that the color of the carboxymethyl cellulose beads mixed with the copper sulfate solution turned light blue, proving its ability to adsorb heavy metal copper ions.

[0069] Example 4: A method for preparing a high-strength and high-toughness regenerated cellulose hydrogel bead with magnetism, comprising the following steps:

[0070] (1) Cellulose modification: cellulose material is modified by sulfonation to obtain sulfonated cellulose (for the specific modification method, refer to the sulfonation method in the prior art);

[0071] (2) Dissolving cellulose: 10 g of sulfonated cellulose was weighed and dissolved in 90 g of a 6% sodium hydroxide aqueous solution (precooled at 0°C) to obtain a cellulose solution;

[0072] (3) Regenerated cellulose: Mix the dissolved cellulose solution with 1g of ferroferric oxide particles and pour them into a syringe. Load the syringe with a peristaltic pump and slowly drip the cellulose solution into 10% sulfuric acid to obtain black magnetic sulfonic acid cellulose beads. Fig.12 shown.

[0073] Performance Analysis:

[0074] The analysis of magnetic adsorption capacity includes the following steps:

[0075] The magnetic cellulose sulfonate beads prepared in Example 4 were soaked in water and adsorbed on the outside using a magnet. The results are as follows: Fig.13 As shown, according to Fig.13 It can be seen that the gel moves toward one side of the magnet, demonstrating the ability of magnetic adsorption.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing high-strength and high-toughness regenerated cellulose hydrogel beads, characterized in that: The following steps are involved: (1) Cellulose modification: The cellulose material is modified by carboxymethylation to obtain carboxymethyl cellulose with a degree of substitution of 0.35; (2) Dissolving cellulose: 10 g of carboxymethyl cellulose with a carboxymethyl substitution degree of 0.35 is weighed and dissolved in 90 g of a 6% sodium hydroxide aqueous solution precooled to 0°C to obtain a cellulose solution; (3) Regenerated cellulose: Pour the dissolved cellulose solution into a syringe, load it onto a peristaltic pump and slowly drip the cellulose solution into 10% sulfuric acid to obtain transparent carboxymethyl cellulose beads.

2. A high-strength and high-toughness regenerated cellulose hydrogel bead, characterized in that: It is prepared by the preparation method as claimed in claim 1.

Citation Information

Patent Citations

  • Preparation method of regenerated cellulose, regenerated cellulose and application of regenerated cellulose

    CN117050200A